Estrategias de atención temprana para niños con autismo - Araujo Reinoso, Génnesis Anahi (2025)
This study examines the limited implementation of appropriate and timely early intervention strategies for children diagnosed with Autism Spectrum Disorder (ASD), a situation that affects their social, communicative, and behavioral development. The research aimed to identify and describe early care methods that promote educational inclusion and improve learning opportunities. The study is relevant because it offers evidence-based psychopedagogical approaches applicable to teachers, families, and educational institutions. A qualitative approach was used, employing a descriptive and interpretive case study design supported by basic, documentary, and field research. Data were collected through semi-structured interviews with teachers and direct observations of the participating child, using instruments validated by experts. The sample included five students with ASD and six teachers from hospital classrooms; one child and three teachers were selected for detailed analysis. Results indicate progress in self-regulation, communication, and social participation through visual supports, structured routines, and positive reinforcement, despite existing limitations in professional training and interdisciplinary collaboration